2008
DOI: 10.1016/j.schres.2008.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and current autistic features in adolescents with schizotypal personality disorder

Abstract: The diagnostic boundaries between autistic-and schizophrenia-spectrum disorders have varied over the years, and some overlap in diagnostic criteria persists. The present study examined childhood and current signs of autistic disorder (AD) in adolescents with schizotypal personality disorder (SPD) or other personality disorders, as well as healthy controls. A structured interview was administered to rate participants' current symptoms. Participants' guardians were interviewed with the Autism Diagnostic Inventor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 36 publications
3
57
1
1
Order By: Relevance
“…In terms of ventricular indices of global brain maturational differences, early or later immune activation may shift development along a path which is more 'schizophrenia-like' or more 'autism-like', respectively. However, the shared aspects of the early and late phenotype described in mouse models mirror well the many shared features of neurodevelopmental conditions such as autism and schizophrenia [31,34,47,48] .…”
Section: Postnatal Phenotype Depends Upon the Timing Of Prenatal Expomentioning
confidence: 80%
See 1 more Smart Citation
“…In terms of ventricular indices of global brain maturational differences, early or later immune activation may shift development along a path which is more 'schizophrenia-like' or more 'autism-like', respectively. However, the shared aspects of the early and late phenotype described in mouse models mirror well the many shared features of neurodevelopmental conditions such as autism and schizophrenia [31,34,47,48] .…”
Section: Postnatal Phenotype Depends Upon the Timing Of Prenatal Expomentioning
confidence: 80%
“…Indeed, autism was originally referred to as a 'schizophrenic syndrome of childhood' or 'childhood psychosis', and has been suggested to lie on the same spectrum as schizophrenia [34,47] . One way to conceptualize this is to consider that it is not the autistic or schizophrenic condition itself which is inherited, but rather altered neurodevelopment [48] .…”
Section: Introductionmentioning
confidence: 99%
“…Actually, many studies have indicated that there is a phenomenological overlap between ASD and the above-mentioned personality disorders [36, [104][105][106]. Nevertheless, borderline personality disorder (BPD) as a cluster B personality disorder seems to be an important psychiatric comorbidity that can mask autistic features and easily lead to misdiagnosis of ASD patients, as shown in Table 1.…”
Section: Asd and Personality Disordersmentioning
confidence: 99%
“…Findings in the literature indicate that adolescents with schizotypal PD showed significantly more severe current and past autistic features in the areas of social functioning and eccentric interests and behaviors compared to healthy controls and other personality disorder controls (Esterberg et al 2008). The other symptoms of schizotypal PD include lack of close friends (Olin et al 1997), cognitive distortions (Trotman et al 2006), social anxiety, poor educational achievement, paranoid ideation, odd thinking, speech without incoherence, odd beliefs and magical thinking (APA 2000).…”
Section: Precursor Symptomsmentioning
confidence: 99%